Errorless and trial-and-error learning of object locations in patients with executive deficits after brain injury. Issue 2 (7th February 2023) - Scheper, Inge; Kessels, Roy P. C.; Brazil, Inti A.; Bertens, Dirk
ABSTRACT: Studies investigating the efficacy of errorless learning (EL), a rehabilitation method in which the occurrence of errors during learning are eliminated, have predominantly involved patients with memory impairment. However, the most recent perspective on the underlying mechanism of EL explicitly takes executive processes into account. The aim of this study was to investigate whether EL of object locations is beneficial for memory performance compared to trial-and-error learning (TEL) in patients with acquired brain injury (ABI) experiencing executive deficits ( N  = 15) and matched healthy controls ( N  = 15). Participants completed an EL and TEL condition of a computerized spatial learning task, in which the location of everyday objects had to be memorized. The number of errors made during learning was predetermined, varying from 0 (EL condition) to 1, 2, 3, 4 or 5 errors (TEL condition). Results showed a beneficial effect of EL on memory performance in both ABI patients and controls ( p  < .001), but this advantage was not larger in ABI patients compared to controls and was not moderated by the amount of errors made during learning.